671 First-in-man mapping and ablation of ventricular tachycardia using a novel ablation catheter with microelectrodes and thermocouples. (8th December 2021) - Compagnucci, Paolo; Cipolletta, Laura; Volpato, Giovanni; Parisi, Quintino; Rita, Enrico; Molini, Silvano; Misiani, Agostino; Valeri, Yari; Stronati, Giulia; Guerra, Federico; Casella, Michela; Dello Russo, Antonio
Abstract: Aims: Catheter ablation (CA) is an important therapeutic option for patients with recurrent ventricular tachycardia (VT). Recently, a novel contact-force sensing catheter (QDOT, Biosense Webster) allowing radiofrequency ablation in a temperature-controlled fashion, equipped with microelectrodes and thermocouples has been developed and tested in very-high power short duration CA of atrial fibrillation. As of today, this catheter has never been used for VT ablation. To describe the safety and short-term clinical performance of the novel QDOT catheter for the ablation of recurrent VT/electrical storm. Methods and results: Case 1: a 43-year-old male patient with prior anterior myocardial infarction (MI), left ventricular (LV) dysfunction with an apical aneurysm, and recurrent VT episodes was admitted to our hospital for CA of VT. The patient underwent high-density electroanatomical mapping of the left ventricle using a multipolar catheter (PentaRay, Biosense Webster), which showed an extensive apical dense scar region, corresponding to the ventricular aneurysm. When the QDOT catheter was advanced in that region, late/fragmented potentials were detected by microelectrodes as well as by conventional electrodes. During the procedure, a sustained VT with right bundle branch block (RBBB)-inferior axis morphology and transition in V2 could be induced. We recorder diastolic fragmented potentials inside the aneurysm, where the novel catheter previously showed late/fragmented potentials; radiofrequency energy delivery with conventional settings (40 W) in that area led to rapid arrhythmia termination (Figure A). At the end of the procedure, VTs were no more inducible. Case 2: a 79-year-old male patient with prior inferior MI, mild LV dysfunction with a 5 cm × 5 cm × 3 cm aneurysm of the basal-mid inferior wall, and two previous CAs for recurrent VT presented to our hospital for electrical storm due to multiple episodes of slow VT (cycle, 470 ms, RBBB morphology, inferior axis, transition in V6), which were refractory to antiarrhythmic drug treatment. We decided to perform redo CA using the QDOT catheter, which revealed long and fragmented low-amplitude diastolic potentials inside the LV aneurysm (Figure B). VT was rapidly terminated by means of radiofrequency energy delivery with usual settings (40 W) in this region, and was no more inducible afterwards. Conclusions: The novel ablation catheter showed favourable manoeuverability in the ventricle, while also allowing a precise characterization of the tachycardia circuitry and of the arrhythmogenic myocardial substrate, which was enhanced by the availability of microelectrodes. We believe that this preliminary experience may pave the way for further assessments of this new technology in the so far unexplored ventricular milieu.